The Impact of GAP-SOP on The Production and Technical Efficiency of Garlic in Temanggung Regency - Aristiyana Nur Tri wardani; Dwidjono Hadi Darwanto (Agro Ekonomi, 2019)
Temanggung regency is the largest garlic producer region in Central Java Province. However, its productivity is still low compared to the other regencies since garlic farmers have not achieved technical efficiency and limitary garlic farming technology.  Hence, it is necessary to investigate whether the input application in the process of garlic production has been at technically efficient level or not. This research aims to determine factors affecting garlic production, the level of technical efficiency and technical inefficiency of garlic farming in Temanggung Regency. The location of the research was determined by using purposive sampling. The sample selection used simple random sampling method with  60 garlic farmers as the respondent. The result shows that production factors such as land area, garlic seed, ZK fertilizer, pesticide and the level of application of garlic GAP-SOP have significant effect on garlic production. The average value of farmer’s technical efficiency is 0,811. It means that respondents in this study have been technically efficient. The socio-economic factors affecting technical inefficiency are the age, the number of worker in a family, the level of education and participation rate within farmer group. The improvement effort of technical efficiency of garlic farming can be done by optimizing the contribution of farmer group as a facility to access information. Therefore, it is able to improve the skills and knowledge of farmers to farm garlic.